1995
DOI: 10.1093/nar/23.6.1050
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin properties of single-stranded DNA containing a GC-rich triplet repeat: (CTG)15

Abstract: Although triplet repeat DNA sequences are scattered throughout the human genome, their biological function remains obscure. To aid in correlating potential structures of these nucleic acids with their function, we propose their classification based on the presence or absence of a palindromic dinucleotide within the triplet, the G + C content, and the presence or absence of a homopolymer. Five classes of double-stranded (ds) triplet repeats are distinguished. Class I repeats, which are defined by the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 67 publications
6
116
1
Order By: Relevance
“…The labeled oligomers were then probed with conformation-sensitive enzymatic agents (S1 nuclease, P1 nuclease, and mung bean nuclease) (65, 71, 77, 78, 80 -82, 84, 97). All three enzymes have been used widely to evaluate ordered and H-bonded pseudo-duplex DNA regions within DNA tracts that are otherwise disordered, random-coil structures (65,71,78,79,97). S1 nuclease from Aspergillus oryzae, a zinc requiring enzyme with an acidic pH optimum, cleaves single-stranded and partially unpaired DNA and is not base-specific (77,78,98).…”
Section: Resultsmentioning
confidence: 99%
“…The labeled oligomers were then probed with conformation-sensitive enzymatic agents (S1 nuclease, P1 nuclease, and mung bean nuclease) (65, 71, 77, 78, 80 -82, 84, 97). All three enzymes have been used widely to evaluate ordered and H-bonded pseudo-duplex DNA regions within DNA tracts that are otherwise disordered, random-coil structures (65,71,78,79,97). S1 nuclease from Aspergillus oryzae, a zinc requiring enzyme with an acidic pH optimum, cleaves single-stranded and partially unpaired DNA and is not base-specific (77,78,98).…”
Section: Resultsmentioning
confidence: 99%
“…These include the 5Ј-CAG-3Ј repeat that is unstable in triplet expansion diseases such as Huntington's disease and myotonic dystrophy (26,28,29,31) and the centromeric satellite sequence (27). Other simple satellites such as the A ϩ T-rich hypervariable sequence in the 3Ј region of the human apolipoprotein B gene (66) also have the potential to form cruciforms and hairpins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the relevant DNA sequences either have unusual properties in the duplex state or adopt unusually stable alternative secondary structures involving single-stranded domains, which alter the course of the ''normal'' cellular DNA chemistry (14). Initial structural and some thermodynamic studies of model poly͞oligonucleotides have indeed indicated that single strands consisting of repeated copies of (CAG) n , (CTG) n , and (CCG) n are able to adopt extensive secondary structures (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28); however, conformational heterogeneity and͞or kinetically trapped metastable states have precluded the determination of reliable thermodynamic data for this important class of DNA sequences (15,(29)(30)(31)(32)(33). The absence of reliable thermodynamic data prevents a rational evaluation of the different models and precludes theoretical predictions as to which sequences may be prone to assume structures that may lead to the disease state (34).…”
mentioning
confidence: 99%